Cost reduction from resolution/improvement of carcinoid syndrome symptoms following treatment with above-standard dose of octreotide LAR. (2nd September 2017) - Huynh, Lynn; Totev, Todor; Vekeman, Francis; Neary, Maureen P.; Duh, Mei S.; Benson, Al B.
Abstract: Aims: To calculate the cost reduction associated with diarrhea/flushing symptom resolution/improvement following treatment with above-standard dose octreotide-LAR from the commercial payor's perspective. Materials and methods: Diarrhea and flushing are two major carcinoid syndrome symptoms of neuroendocrine tumor (NET). Previously, a study of NET patients from three US tertiary oncology centers (NET 3-Center Study) demonstrated that dose escalation of octreotide LAR to above-standard dose resolved/improved diarrhea/flushing in 79% of the patients within 1 year. Time course of diarrhea/flushing symptom data were collected from the NET 3-Center Study. Daily healthcare costs were calculated from a commercial claims database analysis. For the patient cohort experiencing any diarrhea/flushing symptom resolution/improvement, their observation period was divided into days of symptom resolution/improvement or no improvement, which were then multiplied by the respective daily healthcare cost and summed over 1 year to yield the blended mean annual cost per patient. For patients who experienced no diarrhea/flushing symptom improvement, mean annual daily healthcare cost of diarrhea/flushing over a 1-year period was calculated. Results: The economic model found that 108 NET patients who experienced diarrhea/flushing symptom resolution/improvement within 1 year had statistically significantly lower mean annual healthcare cost/patient than patients with no symptom improvement, by $14, 766 ( p  = .03). For the sub-set of 85 patients experiencing resolution/improvement of diarrhea, their cost reduction was more pronounced, at $18, 740 ( p  = .01), statistically significantly lower than those with no improvement; outpatient costs accounted for 56% of the cost reduction ( p  = .02); inpatient costs, emergency department costs, and pharmacy costs accounted for the remaining 44%. Limitations: The economic model relied on two different sources of data, with some heterogeneity in the prior treatment and disease status of patients. Conclusions: Symptom resolution/improvement of diarrhea/flushing after treatment with an above-standard dose of octreotide-LAR in NET was associated with a statistically significant healthcare cost decrease compared to a scenario of no symptom improvement.